Modeling and analysis of the LC filter-integrated quasi Z-source indirect matrix converter for the wind energy conversion system - Maheswari, K. T.; Kumar, C.; Balachandran, Praveen Kumar; Senjyu, Tomonobu (Frontiers in Energy Research, 2023)
A Quasi Z-Source Indirect Matrix Converter (QZSIMC) is proposed in this paper for Permanent Magnet Generator (PMG) based Direct Drive Wind Energy Conversion Systems (DDWECS) to enhance the voltage transfer ratio and also to control the output voltage under various loading conditions. The QZSIMC comprises three Quasi Z-Source (QZS) networks connected between PMG and load through a three-phase Indirect Matrix Converter (IMC). Two different PWM control techniques such as Carrier Based Pulse Width Modulation Technique and Modified Space Vector Pulse Width Modulation Technique are proposed to analyze the performance of QZSIMC. By changing the shoot through time period, the duty ratio of quasi Z-Source network can be increased which in turn increases the boost factor of both QZSIMC without affecting the efficiency of the converter. A closed-loop control system has also been designed to sustain constant parameters at the output. The proposed QZSIMC for PMG based DDWECS along with two different PWM Control Schemes are to be modeled using MATLAB/SIMULINK environment. To validate the simulation results, a 1 kW, 415 V, 50 Hz experimental setup with an FPGA SPARTAN-6 processor has been developed in the laboratory for QZSIMC and the results are investigated based on the parameters such as output voltage, output current, Switching Stress, Boost Factor, inductor current, capacitor voltage, Total Harmonic Distortion.